Associative memory for conceptually unitized word pairs in mild cognitive impairment is related to the volume of the perirhinal cortex. Issue 7 (26th December 2018) - Delhaye, Emma; Mechanic‐Hamilton, Dawn; Saad, Laura; Das, Sandhitsu R.; Wisse, Laura E. M.; Yushkevich, Paul A.; Wolk, David A.; Bastin, Christine
Abstract: Unitization, that is, the encoding of an association as one integrated entity, has been shown to improve associative memory in populations presenting with associative memory deficit due to hippocampal dysfunction, such as amnesic patients with focal hippocampal lesions and healthy older adults. One reason for this benefit is that encoding of unitized associations would rely on the perirhinal cortex (PrC) and thus minimize the need for hippocampal recruitment. Mild cognitive impairment (MCI) is accompanied by a deficit in associative memory. However, unitization has never been studied to explore the potential benefit in associative memory in MCI, maybe because MCI is characterized by PrC pathology. However, the PrC may potentially still function sufficiently to allow for the successful adoption of unitization. In this study, we aimed at assessing whether unitization could attenuate MCI patients' associative memory deficit, and whether the ability to remember unitized associations would be modulated by the integrity of the PrC in MCI patients. Unitization was manipulated at a conceptual level, by encouraging participants to encode unrelated word pairs as new compound words. Participants also underwent a structural MRI exam, and measures of PrC were extracted (Brodmann Areas [BA] 35 and 36). Results showed that, contrary to healthy controls, MCI patients did not benefit from unitization. Moreover, their memory performance for unitized associations was related to the measure of PrC integrity (BA35), while it was not the case in controls. This finding thus suggests that unitization does not help to attenuate the associative deficit in MCI patients, and brings support to the literature linking unitization to the PrC function.